ChemInform Abstract: Recent Advances in the Synthesis and Electrocatalytic Applications of Platinum‐Based Bimetallic Alloy Nanostructures. Issue 50 (December 2015) - Lai, Jianping; Luque, Rafael; Xu, Guobao
Abstract: Review: 160 refs.